IMPLEMENTASI PERATURAN BUPATI NOMOR 47 TAHUN 2022 TENTANG JAMINAN BONGKAR DALAM PENYELENGGARAAN REKLAME DI KABUPATEN BENGKALIS TAHUN 2023-2024 - Noor, Muhammad Faizal; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the implementation of Bengkalis Regent Regulation Number 47 of 2022 concerning Dismantling Guarantees in Advertising Implementation and its impact on increasing Regional Original Income (PAD) in Bengkalis Regency. This regulation is a regional policy instrument that aims to regulate advertising order and guarantee the contribution of the advertising sector to PAD. The research approach used is qualitative with a case study method. Data were collected through in-depth interviews and documentation of the implementation of policies in the field, especially by the Investment and One-Stop Integrated Service Office (DPMPTSP), the Regional Revenue Agency (Bapenda), and advertising business actors. The results of the study show that the implementation of the Regent Regulation still faces various challenges, including limited human resources, low compliance of business actors, and weak supervision and coordination between agencies. However, this policy has the potential to increase PAD if supported by consistent law enforcement, digitalization of licensing, and ongoing socialization to the community and business actors. With improvements in the implementation aspect, Regent Regulation Number 47 of 2022 can be a strategic instrument in optimizing the contribution of the advertising sector to regional finances. Keyword: Policy implementation, unloading guarantee, Advertising, PAD.